Cannabidiol for at risk for psychosis youth: A randomized controlled trial. Issue 4 (30th June 2021) - Amminger, G. Paul; Lin, Ashleigh; Kerr, Melissa; Weller, Amber; Spark, Jessica; Pugh, Charlotte; O'Callaghan, Sally; Berger, Maximus; Clark, Scott R.; Scott, James G.; Baker, Andrea; McGregor, Iain; et al.
Abstract: Background: No biological treatment has been firmly established for the at‐risk stage of psychotic disorder. In this study we aim to test if subthreshold psychotic symptoms can be effectively treated with cannabidiol (CBD), a non‐psychoactive compound of the plant Cannabis sativa . The question has taken on increased importance in the wake of evidence questioning both the need and efficacy of specific pharmacological interventions in the ultra‐high risk (UHR) for psychosis group. Methods: Three‐arm randomized controlled trial of 405 patients (135 per arm) aged 12–25 years who meet UHR for psychosis criteria. The study includes a 6‐week lead‐in phase during which 10% of UHR individuals are expected to experience symptom remission. Participants will receive CBD (per oral) at doses 600 or 1000 mg per day (fixed schedule) for 12 weeks. Participants in the third arm of the trial will receive matching placebo capsules. Primary outcome is severity of positive psychotic symptoms as measured by the Comprehensive Assessment of At‐Risk Mental States at 12 weeks. We hypothesize that CBD will be significantly more effective than placebo in improving positive psychotic symptoms in UHR patients. All participants will also be followed up 6 months post baseline to evaluate if treatment effects are sustained. Conclusion: This paper reports on the rationale and protocol of the Cannabidiol for At Risk for psychosis Youth (CanARY) study. This study will test CBD for the first time in the UHR phase of psychotic disorder.